EFEITO DA APLICAÇÃO VIBRATÓRIA E DA UMIDADE DENTINÁRIA NA LONGEVIDADE DE SISTEMAS ADESIVOS CONVENCIONAIS DE DOIS PASSOS - Zander-grande, Christiana (2008)
The purpose of this study was to evaluate the effects of different application modes and moisture degree on the resin-dentin bond strength values and nanoleakage pattern on the immediate and 6-month time. An ethanol/water based (Single Bond [SB]) and an acetone-based system (One Step [OS]) was used. On 32 third molars, a flat superficial dentin surface was exposed by wet abrasion. After the acid etching (15 s) and rinse (30 s), two coats of the adhesive were applied on either a dry [D] or rewetted surface [W], under slight rubbing action [S] without manual pressure or vibratory mode [V] with a vibratory prototype applicator. An air stream for 10 s at a distance of 20 cm was used after the adhesive application. The specimens were light curing (800 mW/cm2/10 s), composite build-ups were constructed incrementally and specimens were stored in water (37 °C/24 h). They were longitudinally sectioned in the “x” and “y” directions to obtain bonded sticks (0.8 mm2) to be tested in tension at 0,5 mm/min. The data was analyzed by a three-way ANOVA and Tukey’s multiple comparison test (α = 0.05). For the nanoleakage analysis the sticks were coated with two layers of nail varnish applied up to within 1 mm of the bonded interfaces. The specimens were placed in the ammoniacal silver nitrate in darkness for 24 h, rinsed with distilled water, and immersed in photo developing solution for 8 h under a fluorescent light. All sticks were embedded in acrylic resin. The samples were wet-polished. Resin-dentin interfaces were analyzed in a field-emission scanning electron microscope to determine the nanoleakage pattern and adhesive layer thickness. For the resin-dentin bond strength values, the moisture of the substrate was not significant for SB however a moist substrate was essential for the OS adhesive. The vibratory application did not affect the immediate bond strength values for both adhesives, however this method prevented the SB system from degradation. The vibratory application reduced significantly the adhesive layer thickness of the OS and practically did not affect the thickness of the SB system. The qualitative analyze suggested lower infiltration of silver nitrate when the vibratory mode application was used, the same did not occur for OS. Based on the results of this study it was concluded that: 1) After six months of water storage, reductions in bond strength values and intense silver penetration were not observed under VB application in compare with SU application, 2) Less sensibility for moist was attributed to SB, 3)In the OS groups high bond strength values were obtained in moist dentin, 4) In the OS groups a considerable degradation was observed.